2016
DOI: 10.1097/md.0000000000002569
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Pancreatic Amylase Value on Postoperative Day 1 After Pancreatic Resection to Predict Postoperative Pancreatic Fistula

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Previous studies1417 by Tsujie et al17 have reported that patients with low drain amylase level on post-operative day 1 are safe from developing POPF 16. This translates to improved confidence in removing surgically-placed pancreatic drains at POD 3, in patients with low drain amylase values at POD 1 and 3.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies1417 by Tsujie et al17 have reported that patients with low drain amylase level on post-operative day 1 are safe from developing POPF 16. This translates to improved confidence in removing surgically-placed pancreatic drains at POD 3, in patients with low drain amylase values at POD 1 and 3.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies identified a patient with pancreatic fistula after radiological confirmation, before using ISGPF classification to stratify POPF. Others used drain amylase value cut-offs >1000 U/L to >4000 U/L on POD 1, to define POPF 16. In our study, biochemistry was used as primary assessment for presence of POPF, and only patients with clinical signs and biochemically raised drain amylase value at POD 3 or after, had computed tomography to confirm presence of POPF.…”
Section: Discussionmentioning
confidence: 99%
“…Visual changes in the appearance of the drain fluid only become evident from postoperative day 5 22 , whereas amylase levels in the drain fluid increase already on postoperative day 1 due to its early and imperceptible extravasation through the anastomosis. Several cutoff values of DFA 1,6,8,[14][15][16][17]22,25 , ranging from 90 14 to 5,000 U/L 22 , have been described for determining the high risk of developing CR-POPF. The most cited cutoff value is 5,000 U/L 22 , thus motivating surgeons to remove the abdominal drain early when DFA values are below the aforementioned cutoff 28 .…”
Section: Central Messagementioning
confidence: 99%
“…Several studies 22,24,32 have pointed out the importance of measuring the aFRS and DFA. With varying diagnostic values 1,6,8,[14][15][16][17]22,24,25 , the determination of these scores facilitates a more individualized management, considering if the patient is at low or high risk of developing CR-POPF 4,12,18,24,30 . However, there is still no consensus on which of these scores is better and whether combining both scores would result in increased accuracy in the selection of patients with a high risk of developing CR-POPF.…”
Section: Central Messagementioning
confidence: 99%
“…Therefore, the markers for pancreatic function may be used as predictors of the development of post-operative complications after Whipple resection. Several studies [8][9][10][11] have shown an association between amylase levels in drains and serum with post-operative complications after pancreaticoduodenectomy.…”
Section: Introductionmentioning
confidence: 99%